2018
DOI: 10.1590/s0102-865020180050000003
|View full text |Cite
|
Sign up to set email alerts
|

Influence of oophorectomy on glycemia and lipidogram

Abstract: Oophorectomy was related to dyslipidemia and insulin resistance, mainly after 50th days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
2
2
0
Order By: Relevance
“…n for each group is in the column skeletal muscle of male mice predominate the estrogen receptor beta, that reduces the expression of the GLUT4 (Barros et al, 2006(Barros et al, , 2009. Different studies in female rats submitted to ovariectomy found that they have insulin resistance and glucose intolerance (Faulds et al, 2012;Kleber Costa Teixeira et al, 2018;Saengsirisuwan et al, 2009). Here, we show for the first time that glucose curve during GTT in 18-month-old female rats is similar to younger counterparts (Figure 2b,c).…”
Section: Discussionsupporting
confidence: 58%
“…n for each group is in the column skeletal muscle of male mice predominate the estrogen receptor beta, that reduces the expression of the GLUT4 (Barros et al, 2006(Barros et al, , 2009. Different studies in female rats submitted to ovariectomy found that they have insulin resistance and glucose intolerance (Faulds et al, 2012;Kleber Costa Teixeira et al, 2018;Saengsirisuwan et al, 2009). Here, we show for the first time that glucose curve during GTT in 18-month-old female rats is similar to younger counterparts (Figure 2b,c).…”
Section: Discussionsupporting
confidence: 58%
“…However, in the groups without ERT, after 20 weeks postovariectomy LDL values were decreased compared to those at 10 weeks. In agreement with our results, Teixeira et al [75] found temporal variations in LDL, cholesterol, and HDL after ovariectomy. Thus, our results confirm that ovariectomy induces time-dependent lipid metabolic alterations.…”
Section: Metabolic Alterations Caused By Ovariectomy and The Effect O...supporting
confidence: 94%
“…The ovariectomy itself resulted in an increase in triglyceride levels. The higher triglyceride levels could be associated with the lack of sex hormones such as in menopause 19 . After treating OVX animals with pilocarpine, there was a significant decrease in triglycerides in the 30 min (90.40 ± 21.58 mg/dL) and 90 min (54.60 ± 16.30 mg/dL) of SE onset, compared to CTR-OVX (214.50 ± 43.00 mg/dL) ( Fig.…”
Section: Resultsmentioning
confidence: 99%